Peran Kepemimpinan dalam Meningkatkan Kinerja Pegawai di Dinas Ketahanan Pangan Provinsi Papua Barat - Idie, Dorce; Sutrisno, Sutrisno; Indiati, Indiati (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to determine the role of leadership in improving employee performance at the West Papua Provincial Food Security Office. The research method used is descriptive qualitative research, which is research that describes narratively based on the data of research results that are objectively analyzed from the results of interviews, observations, and document reviews. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. As a result of the data analysis, it was concluded that the performance of employees at the West Papua Provincial Food Security Service had improved and was quite well implemented by the employees. Performance issues always receive attention in management because they are closely related to the productivity of an institution or organization. In this regard, efforts to conduct performance assessments are very important. It is recognized that many people are able but unwilling, so they still do not produce optimal performance.